PENGARUH PENANAMAN MODAL ASING DAN UTANG LUAR NEGERI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Rahmat Arsyad (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2019)
This study aims to know how the influence of Foreign Investment and Foreign Debt on economic growth in Indonesia. This research uses data from Bank Indonesia (BI) and Central Statistics Agency (BPS) Publication reports. The data analysis method used is multiple linear regression. Before using this method, the data must be tested with the classic assumption test that is normality test and other tests. The observation period is from 2010 to 2017. Based on the normality test, the data is normally distributed, and the classical assumptions are fulfilled means that we can use multiple linear regression methods. The results showed that foreign investment had a significant effect on economic growth in Indonesia, while foreign debt did not significantly influence Indonesia's economic growth. The predictive ability for the two independent variables on Economic Growth in this study is around 66.2%, while the rest is influenced by other factors